2021
DOI: 10.1093/cid/ciab792
|View full text |Cite
|
Sign up to set email alerts
|

South Indian Children’s Neurodevelopmental Outcomes After Group B Streptococcus Invasive Disease: A Matched-Cohort Study

Abstract: Introduction This study is part of a multi- country matched cohort study designed to estimate the risk of long term neurodevelopmental of children exposed to iGBS. The specific objective of this paper is to compare NDI across domains of iGBS survivors with a matched non-GBS group in our population. Methods Survivors of iGBS in a south Indian hospital were identified and recruited between January 2020 and April 2021. Cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, this pathogen is also associated with other health outcomes [2] (Fig. 1), including as a causative factor for stillbirths [3], and a risk factor for preterm births [4] and for long-term sequelae in survivors of acute disease [5,6 ▪▪ ,7,8,9 ▪ ,10 ▪▪ ]. It was estimated that 46,200 (95% posterior interval 20,300–111,300) stillbirths resulted from in utero GBS infection in 2020, and up to 518,100 (36,900–1142,300) preterm births might have been associated with GBS colonisation [1 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this pathogen is also associated with other health outcomes [2] (Fig. 1), including as a causative factor for stillbirths [3], and a risk factor for preterm births [4] and for long-term sequelae in survivors of acute disease [5,6 ▪▪ ,7,8,9 ▪ ,10 ▪▪ ]. It was estimated that 46,200 (95% posterior interval 20,300–111,300) stillbirths resulted from in utero GBS infection in 2020, and up to 518,100 (36,900–1142,300) preterm births might have been associated with GBS colonisation [1 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Danish cohort comprised fewer infants born preterm (21% vs 31% in our study) and included cases not confirmed by culture 9 . Four studies from low‐income countries reported that 27.9% to 50.0% of infants surviving GBS infection had any neurodevelopmental impairment 28–31 . In total, 273 children with invasive GBS infection during infancy were included in these studies, and the follow‐up ranged from 1 to 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…9 Four studies from low-income countries reported that 27.9% to 50.0% of infants surviving GBS infection had any neurodevelopmental impairment. [28][29][30][31] In total, 273 children with invasive GBS infection during infancy were included in these studies, and the follow-up ranged from 1 to 18 years. Despite different estimates, the main results of these studies as well as those reported by Kadambari et al and Horváth-Puhó et al agree with our findings, indicating a substantial burden of NDDs following invasive GBS infection.…”
Section: Eodmentioning
confidence: 99%
“…A cohort study of GBS meningitis survivors in the United States assessed children younger than 6 years using the Mullen Scales of Early Learning to assess language, motor and cognitive ability. A similar study in children from South India showed that survivors of invasive GBS infection had greater motor impairment compared to age-matched children who were not exposed to GBS ( John et al, 2022 ). Impaired neurologic functioning was observed in 50% (9/18) of patients and 28% (5/18) experiencing severe impairment ( Libster et al, 2012 ).…”
Section: Clinical Outcomes and Risk Factors Associated With Early-ons...mentioning
confidence: 93%